(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the effect of using short reports on the achievement of intermediate first-grade students in the subject of the history of ancient Iraq. In order to investigate this, the researcher chose Al-Izdihar Secondary School for Girls affiliated to the Directorate of Education of Diyala, which contains two divisions for the first intermediate grade, if the number of female students in the two groups reached (48). Student, the students of the experimental group studied using short reports and the control group in the usual way used in teaching history